Answer Distillation Network With Bi-Text-Image Attention for Medical Visual Question Answering - Hongfang Gong; Li Li (IEEE Access)
Medical Visual Question Answering (Med-VQA) is a multimodal task that aims to obtain the correct answers based on medical images and questions. Med-VQA, as a classification task, is typically more challenging for algorithms to predict answers to open-ended questions than to closed-ended questions due to the larger number of answer categories for the former. Consequently, the accuracy of predictions for open-ended questions is generally lower than that for closed-ended questions. In this study, we design answer distillation network with bi-text-image attention (BTIA-AD Net) to solve the above problem. We present an answer distillation network to refine the answers and convert an open-ended question into a multiple-choice question with a selection of candidate answers. To fully utilize the candidate answer information from answer distillation network, we propose a bi-text-image attention fusion module composed of self-attention and guided attention to automatically fuse image features, question representations, and candidate answer information and achieve intra-modal and inter-modal semantic interaction. Extensive experiments validate the effectiveness of BTIA-AD Net. Results prove that our model can efficiently compress the answer space of open-ended tasks, improve the answer accuracy, and provide new state-of-the-art performance on the VQA-RAD dataset.